Quality of Healthcare Services in the Tengger Tribe Community of Ranu Pane Village - Sakir Sakir; Akhmad Habibullah (Universitas Muhammadiyah Yogyakarta, 2019)
One of the primary functions of the state is to provide public services. Through their authority, the state is required to provide excellent service, in order to respond to public demands which gets increasingly complex. Ideally, high-quality public services should not only be given to people in the urban areas, but also towards marginalized people, including isolated indigenous communities. This study intends to determine the extent of the quality of the public services provided to the Tengger Tribe community in Probolinggo Regency, East Java. The research is conducted in Ranupane Village, Probolinggo Regency. And the research method used is qualitative method, with the techniques for collecting data are interviews, observation and documentation. Results showed that the quality of healthcare services for the people of Tengger Tribe was not optimal. The influential factors are local culture, geographical location, infrastructure and the quality of government official resources. As for the recommendations offered are for the regional government to give an optimal healthcare service, through the placement of health workers (doctors, nurses, midwives) with adequate experience, repair infrastructures and build health facilities on Maternity Cottage (Polindes) and Assisting Health Center (Pustu) level, and creating innovation in healthcare specifically for marginalized communities like the Tengger Tribe and other tribes in Indonesia, in order to create a synchronization between medical and non-medical treatments.